2016
DOI: 10.18632/oncotarget.8084
|View full text |Cite
|
Sign up to set email alerts
|

Divergent branches of mitochondrial signaling regulate specific genes and the viability of specialized cell types of differentiated yeast colonies

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 42 publications
1
38
0
1
Order By: Relevance
“…Whereas upper cells are glycolytic with a low respiratory metabolism, lower cells behave oppositely (Palková et al, 2014;Čáp et al, 2015). Lower cells can be further stratified into "upper" and "lower" lower cells (Podholová et al, 2016).…”
Section: Csr2 Regulates Hxt6 Homeostasis In the Context Of A Yeast Comentioning
confidence: 99%
“…Whereas upper cells are glycolytic with a low respiratory metabolism, lower cells behave oppositely (Palková et al, 2014;Čáp et al, 2015). Lower cells can be further stratified into "upper" and "lower" lower cells (Podholová et al, 2016).…”
Section: Csr2 Regulates Hxt6 Homeostasis In the Context Of A Yeast Comentioning
confidence: 99%
“…Activation, by RTG gene-dependent retrograde signaling (RTG signaling), of expression of genes (such as CIT2 ) involved in anaplerotic pathways was described many years ago in yeast cells grown in liquid cultures [ 15 , 16 ]. However, we recently showed that RTG signaling in colonies is more complex than that described previously and activates expression of different genes in differentiated cells [ 17 ]. We identified three branches of RTG signaling that are specific to U cells (the Ato branch), the upper subpopulation of L cells (the Cit2 branch), and the lower subpopulation of L cells (the cell-viability branch).…”
Section: Introductionmentioning
confidence: 99%
“…We identified three branches of RTG signaling that are specific to U cells (the Ato branch), the upper subpopulation of L cells (the Cit2 branch), and the lower subpopulation of L cells (the cell-viability branch). These signaling branches regulate different gene targets and/or contribute differently to viability of each of the three subpopulations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas laboratory and domesticated yeast strains form smooth colonies of cells that do not invade the agar and can be separated relatively easily [ 9 , 25 ], wild yeast strains form complex colony biofilms with features of natural biofilms. Cells within colony biofilms are connected by extracellular fibers, and the lower parts of colonies (“roots”) are formed by pseudohyphae.…”
Section: Discussionmentioning
confidence: 99%